iPad 2 made simple - Trautschold, Martin; Mazo, Gary (Apress, 2011)
The iPad 2 is thinner, more powerful, intuitive and very fun for users of all ages. Your iPad can be used for reading, surfing the web, emailing, watching TV and movies, getting work done and much more. And with over 65,000 apps just for the iPad, as well as the ability to run over 30,000 iPhone apps, the possibilities are endless. iPad 2 Made Simple clarifies all of the key features on the iPad, introduces what’s new, and also reveals dozens of time-saving shortcuts and techniques. The book has over 1,000 screen shots that are carefully annotated with step-by-step instructions. Clear instructions on how to set up and use the iPad. Illustrated explanations of all the key features. Hundreds of graphics as well as tips and tricks.